Robustness analysis and experimental validation of a fault detection and isolation method for the modular multilevel converter - Shao, Shuai; Watson, Alan James; Clare, Jon C.; Wheeler, Patrick (IEEE, 2016)
This paper presents a fault detection and isolation (FDI) method for open-circuit faults of power semiconductor devices in a modular multilevel converter (MMC). The proposed FDI method is simple with only one sliding mode observer (SMO) equation and requires no additional transducers. The method is based on an SMO for the circulating current in an MMC. An open-circuit fault of power semiconductor device is detected when the observed circulating current diverges from the measured one. A fault is located by employing an assumption-verification process. To improve the robustness of the proposed FDI method, a new technique based on the observer injection term is introduced to estimate the value of the uncertainties and disturbances, this estimated value can be used to compensate the uncertainties and disturbances. As a result, the proposed FDI scheme can detect and locate an open-circuit fault in a power semiconductor device while ignoring parameter uncertainties, measurement error and other bounded disturbances. The FDI scheme has been implemented in a field programmable gate array (FPGA) using fixed point arithmetic and tested on a single phase MMC prototype. Experimental results under different load conditions show that an open-circuit faulty power semiconductor device in an MMC can be detected and located in less than 50ms.